On Risk of Rain on Snow Over High‐Latitude Coastal Areas in North America - Azharuddin Mohammed; Ardeshir Ebtehaj; Judah Cohen; Efi Foufoula‐Georgiou (Geophysical Research Letters)
Abstract Extreme floods and landslides in high‐latitude watersheds have been associated with rain‐on‐snow (ROS) events. Yet, the risks of changing precipitation phases on a declining snowpack under a warming climate remain unclear. Normalizing the total annual duration of ROS with that of the seasonal snowpack, the ERA5 data (1941–2023) show that the frequency of high‐runoff ROS events is a characteristic feature of high‐latitude coastal zones, particularly over the coasts of south‐central Alaska and southern Newfoundland. Total rainfall accumulation per seasonal snowpack duration has increased across western mountain ranges, with the Olympic Mountains experiencing more than 40 mm of additional rainfall over the snowpack in the past eight decades, followed by the Sierra Nevada. These trends could drive an 8% increase in rainfall extremes (e.g., more than 10 mm for 6 hr storm with a 15‐year return period), highlighting the need for resilient flood control systems in high‐latitude coastal cities.